Pendidikan Profetik dalam Novel Bumi Cinta Karya Habiburrahman El Shirazy dan Implikasinya pada Capaian Pembelajaran PAI Kurikulum Merdeka - Neng Susilawati; Ayi Sobarna; Heru Pratikno (UNISBA Press, 2023)
Abstract. Education is the link to make humans bring out their best potential. Islamic education has an important role in overcoming the degradation of the eastern values of the Indonesian nation. Islamic education aims to guide humans as the best of God's creatures and make perfect humans (insan kamil). Islamic education that positions the Prophet Muhammad as an ideal figure in exemplary morals is interpreted as prophetic education. This study discusses the form of prophetic education in the novel Bumi Cinta by Habiburrahman El Shirazy and its implications for the PAI Learning Outcomes of the Merdeka Curriculum. The research method used is descriptive method by using documentation techniques in collecting data and using content analysis techniques in analyzing the data that has been obtained. Based on the results of research and discussion, the value of prophetic education in the novel Bumi Cinta by Habiburrahman El Shirazy is the value of humanization including brotherhood, justice, and mutual respect; the value of liberation includes hurriyah (self-liberation from attachment or oppression) and preventing bad behavior; and the value of transcendence includes faith, piety, and sincerity. There are implications between the values of prophetic education in the novel Bumi Cinta by Habiburrahman El Shirazy and the PAI Learning Outcomes of the Kurikulum Merdeka, namely the importance of applying Islamic values in everyday life. In the PAI Learning Outcomes of Kurikulum Merdeka, the values of humanization, liberation, and transcendence are contained in the elements of Al-Qur'an-Hadith, Akidah, Akhlak, Fikih, and History of Islamic Civilization in each learning phase. abstrak. Pendidikan merupakan penghubung untuk menjadikan manusia mengeluarkan potensi terbaiknya. Pendidkan Islam mempunyai peran penting dalam mengatasi degradasi nilai ketimuran bangsa Indonesia. Pendidikan Islam bertujuan memandu manusia sebagai sebaik-baiknya makhluk ciptaan Allah dan menjadikan manusia yang sempurna (insan kamil). Pendidikan Islam yang memposisikan Nabi Muhammad saw sebagai sosok ideal dalam keteladanan akhlak dimaknai sebagai pendidikan profetik (pendidikan kenabian). Penelitian ini membahas tentang bentuk pendidikan profetik dalam novel Bumi Cinta karya Habiburrahman El Shirazy dan implikasinya terhadap Capaian Pembelajaran PAI Kurikulum Merdeka. Metode penelitian yang digunakan adalah metode deskriptif dengan menggunakan teknik dokumentasi dalam pengumpulan data-data serta menggunakan teknik analisis isi (content analysis) dalam menganalisis data yang telah didapatkan. Berdasarkan hasil penelitian dan pembahasan yang dilakukan, nilai pendidikan profetik yang ada di dalam novel Bumi Cinta karya Habiburrahman El Shirazy adalah nilai humanisasi meliputi persaudaraan, adil, dan saling menghargai; nilai liberasi meliputi hurriyah (pembebasan diri dari keterikatan atau penindasan) dan mencegah perilaku kemungkaran; dan nilai transendensi meliputi keimanan, ketakwaan, dan keikhlasan. Terdapat implikasi antara nilai-nilai pendidikan profetik yang ada di dalam novel Bumi Cinta karya Habiburrahman El Shirazy dengan Capaian Pembelajaran PAI Kurikulum Merdeka, yaitu tentang pentingnya menerapkan nilai-nilai keislaman dalam kehidupan sehari-hari. Dalam Capaian Pembelajaran PAI Kurikulum Merdeka, nilai humanisasi, liberasi, dan transendensi dimuat dalam elemen Al-Qur’an-Hadis, Akidah, Akhlak, Fikih, dan Sejarah Peradaban Islam yang ada di setiap fase pembelajaran.